Return to work interventions for chronic pain: a systematic review. (25th May 2020) - Wegrzynek, P A; Wainwright, E; Ravalier, J
Abstract: Background: Chronic pain (CP) remains the second commonest reason for being off work. Tertiary return to work (RTW) interventions aim to improve psychological and physical capacity amongst workers already off sick. Their effectiveness for workers with CP is unclear. Aims: To explore which tertiary interventions effectively promote RTW for CP sufferers. Methods: We searched eight databases for randomized controlled trials evaluating the effectiveness of tertiary RTW interventions for CP sufferers. We employed the Cochrane Risk of Bias (ROB) and methodological quality assessment tools for all included papers. We synthesized findings narratively. Meta-analysis was not possible due to heterogeneity of study characteristics. Results: We included 16 papers pertaining to 13 trials. The types, delivery format and follow-up schedules of RTW interventions varied greatly. Most treatments were multidisciplinary, comprising psychological, physical and workplace elements. Five trials reported that tertiary interventions with multidisciplinary elements promoted RTW for workers with CP compared to controls. We gave a high ROB rating for one or more assessment criteria to three out of the five successful intervention trials. Two had medium- and low-risk elements across all categories. One compared different intensity multidisciplinary treatment and one comprised work-hardening with a job coach. Seven trials found treatment effects for secondary outcomes but no RTW improvement. Conclusions: There is no conclusive evidence to support any specific tertiary RTW intervention for workers with CP, but multidisciplinary efforts should be considered. Workers' compensation is an important area for RTW policymakers to consider.